The floristic diversity of the landscape protected area nature reserve “Ridges of Luchshevo village” (Kemerovo region, Kuzbass) - T. O. Strelnikova; A. N. Kupriyanov; S. A. Sheremetova; I. A. Khrustaleva; O. A. Kupriyanov (Проблемы ботаники Южной Сибири и Монголии, 2021)
The results of a floristic study of the “Ridges of Luchshevo village” reserve (Kemerovo region -Kuz-bass) are presented. On the area of 960.7 hectares, 456 species of vascular plants belonging to 69 families werefound. This territory is home to 8 species listed in the Red Data Book of the Kemerovo Region: Adonis villosa, Alliumvodop-janovae, Cypripedium calceolus, C. macranthon, Erythronium sibiricum, Stipa pennata, S. zalesskii,Polystichum brau-nii.